Perancangan Interior Sekolah Dasar Montessori di Surabaya - Hedy C. Indrani, Silviana Sampurna Tanzil (Intra, 2013)
Elementary School which applied Montessori system for children is one of the design project for intending to develop chilsâs interest and talent are packed in teaching and learning activities that are educational and fun. Considering elementary school to be main major for child, of course that will bring some impression in theÂ process of child intelligence. Therefore, the integration of the formal and non formal education system will be special characteristic that may support child in teaching dan learning activity. Design arragement impresses dynamic in order to make children more enthusiastic and active in all processes. Absolutely it would be relevant to the needs of child around the age of 6-12 years, either the condition dan character of the child. Design methods using qualitative applied starting from exploration to final design that can accommodate the facilities needed by the child in accordance with the Montessori method.